Innovative Technologies to Support Education and Training: Researches by LabTEVE - Machado, Liliane; Moraes, Ronei (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
Training systems based on virtual reality, serious games, assessment methods, systems to support learning, assessment methodologies and technologies to extend interaction with educational content have been the focus of researches at LabTEVE. The interdisciplinarity can be observed in each project, highlighting the need for dialogue between areas for the production of solutions and technologies that can be used today as well as prospected for the future.